Analysis of brain signal change response in amygdala evoked by skin pressure stimulus. Issue 1 (17th November 2022) - Yuan, Jie; Wang, Qicai; Shang, Shanshan; Lei, Yutian; Lou, Lin
Abstract: Background: It was well known that the human body would produce an uncomfortable sensation when the fabric exerted a certain amount of pressure irritation on the skin. The amygdala had long been thought to be the source of negative emotion perception. However, up to now, the brain signal changes in the amygdala evoked by skin exposure pressure had not been known. Materials and methods: In this work, a series of gradually increasing contact pressure stimulus from boneless corsets was repeatedly applied to the body's waist and abdomen, and the technology of functional magnetic resonance imaging (fMRI) was adopted to detect the brain response synchronously. Results: The results shown that both subjective comfort score and percent signal changes (PSCs) of amygdala decreased with the increase of skin contact pressure. When the skin pressure applied to the waist and abdomen of the human body exceeded about 1 kPa, blood oxygen level dependent signal in the amygdala was negatively activated. Besides, the degree of response of PSCs was intense than subjective evaluation, and the standard deviations of PSCs between individuals were much smaller than subjective evaluations. Conclusion: It was suggested that skin contact pressure stimulus caused the attention of the amygdala brain area. The greater the stimulus, the higher the attention, but such attention was caused by negative activation of the amygdala induced by skin discomfort. In addition, skin comfort representation based on brain perception was superior to subjective representation due to its higher response sensitivity and antipsychological interference ability.